2022
DOI: 10.1177/10556656221100679
|View full text |Cite
|
Sign up to set email alerts
|

UCSQ Method Applied on 3D Photogrammetry: Non-Invasive Objective Differentiation Between Synostotic and Positional Plagiocephaly

Abstract: Objective Objective differentiation between unilateral coronal synostosis (UCS) and positional posterior plagiocephaly (PPP) based on 3D photogrammetry according to Utrecht Cranial Shape Quantificator (UCSQ). Design Retrospective study. Setting Primary craniofacial center. Patients, Participants Thirty-two unoperated patients (17 UCS; 15 PPP) (age < 1 year). Interventions Extraction of variables from sinusoid curves derived using UCSQ: asymmetry ratio forehead and occiput peak, ratio of gradient forehead an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Two publications use sinusoidal curves to show the contour of the cranial shape at an axial slice 53,54 . Based on the sinusoidal curves, patterns for types of craniosynostosis are distinguished.…”
Section: Resultsmentioning
confidence: 99%
“…Two publications use sinusoidal curves to show the contour of the cranial shape at an axial slice 53,54 . Based on the sinusoidal curves, patterns for types of craniosynostosis are distinguished.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to radiation, the need for the sedation of the infants would increase the risk for the examinee even further, again highlighting the insufficiency of CT as a primary diagnostic tool in this patient group. It should therefore be reserved for cases where synostosis could not be ruled out otherwise [11,16,21,32]. Consequently, a radiation-free alternative to CT was needed and found in 3D digital photography, as Mendonca et al could show that both methods produce interchangeable measurement results [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It should therefore be reserved for cases where synostosis could not be ruled out otherwise [11,16,21,32]. Consequently, a radiation-free alternative to CT was needed and found in 3D digital photography, as Mendonca et al could show that both methods produce interchangeable measurement results [31,32]. In performing their manual and digital measurements on mannequins and, therefore, equal standardized settings, Weinberg et al also confirmed that 3D digital photography is sufficiently concordant, accurate, and precise compared with CT, which makes it consequently suitable for clinical use [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation